Outcomes of Anlotinib Maintenance Therapy in Patients With Advanced NSCLC in a Real-World Setting - Li, Jia; Han, Baohui; Liu, Huaimin (Frontiers in Oncology, 2022)
Background: Anlotinib is a novel tyrosine kinase inhibitor with promising anti-tumor activity in patients with advanced non-small cell lung cancer (NSCLC). The aim of this study was to evaluate the efficacy and safety of anlotinib maintenance therapy in patients with advanced NSCLC in real-world situation. Methods: We conducted a retrospective study on the patients with stage IIIb or IV NSCLC who visited our hospital between December 2016 and April 2020. They achieved an objective response or stable disease after first- or second- line treatment and then received switch maintenance therapy with anlotinib. Data were collected using automated data mining technology from electronic health records. Patients’ demographic and clinical characteristics, median progression-free survival (PFS), median overall survival (OS), and adverse events were described, and preliminary analysis of efficacy predictors was analyzed. Results: Thirty-two patients were included in this study (20 patients in first-line treatment and 12 patients in second-line treatment). Median anlotinib maintenance time was 9 days (Q1-Q3: 3-22). The median PFS was 11.5 months, with 11.5 months in first-line treatment and 8.9 months in second-line treatment. The median OS was 12.0 months, with 16.4 months in first-line treatment group and 8.9 months in second-line treatment group. Grade 2-3 treatment-related adverse events were reported in 18.76% patients. No life-threatening adverse events were observed. Conclusion: Our results suggested that anlotinib maintenance therapy might be a potentially safe and efficacious option for patients who had benefited from first- or second-line treatment. However, our data are limited representative due to the small sample size; the efficacy of anlotinib maintenance therapy warrants further evaluation.